2019
DOI: 10.1371/journal.pone.0219506
|View full text |Cite
|
Sign up to set email alerts
|

Why video health education messages should be considered for all dental waiting rooms

Abstract: Objective Video is an effective, accessible, and low cost method of delivering health education messages to a wide audience. Dental waiting rooms provide an opportunity to deliver video oral health education interventions to receptive viewers. In this study we aim to evaluate firstly video oral health education in regards to patient preference, and secondly its ability to change both immediate and sustained self-reported intended health behaviours by patients. Method Da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 29 publications
1
25
0
1
Order By: Relevance
“…This communication method has proven to be easy to understand, practical, and leads to a better patient waiting experience while decreasing anxiety. The 52% decrease in pre-exam anxiety in our study is in line with results found in literature [14][15][16][17].…”
Section: Discussionsupporting
confidence: 93%
“…This communication method has proven to be easy to understand, practical, and leads to a better patient waiting experience while decreasing anxiety. The 52% decrease in pre-exam anxiety in our study is in line with results found in literature [14][15][16][17].…”
Section: Discussionsupporting
confidence: 93%
“…The latter might be ascribed to the ability of PLOS ONE covering many aspects of the treatment in a sufficient way with longer videos [25]. The use of videos for oral health education is an enjoyable and preferred method by patients, however, the fun in learning was previously reported to be more with patients who watched the video from 5 to 20 minutes [30]. This calls for the need of studies evaluating the effect of video length on the usefulness of the presented materials and the engagement of the patient.…”
Section: Discussionmentioning
confidence: 99%
“…This is one of the most important factors for teens to be motivated to learn. The interest of adolescents is increased thanks to the use of graphic and video animation [ 30 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%